B-T phase diagram of Pd/Fe/Ir(111) computed with parallel tempering Monte Carlo - Boettcher, M.; Heinze, Stefan; Egorov, S.; Sinova, Jairo; Dupe, B. (New Journal of Physics, 2018)
We use an atomistic spin model derived from density functional theory calculations for the ultra-thin film Pd/Fe/Ir(111) to show that temperature induces coexisting non-zero skyrmion and antiskyrmion densities. We apply the parallel tempering Monte Carlo method in order to reliably compute thermodynamical quantities and the B-T phase diagram in the presence of frustrated exchange interactions. We evaluate the critical temperatures using the topological susceptibility. We show that the critical temperatures depend on the magnetic field in contrast to previous work. In total, we identify five phases: spin spiral, skyrmion lattice, ferromagnetic phase, intermediate region with finite topological charge and paramagnetic phase. To explore the effect of frustrated exchange interactions, we calculate the B-T phase diagram, when only effective exchange parameters are taken into account.
CRIS-Team Scopus Importer:2023-03-27
Keywords: frustration of magnetic exchange; magnetic skyrmions; Monte Carlo simulations; thermodynamic study